Target financial forecasting as an instrument to improve company financial health - Sergey Krylov (Cogent Business & Management, 2018)
The paper considers conceptual, methodical, and practical aspects of the target financial forecasting at the micro level, i.e. the company level, as a new instrument of anticrisis financial management for a company to overcome its financial difficulties and enhance its financial position within a time-period of practically any length. The methodology of the research, the results being presented in the paper, is based on the concept of the financial ratio analysis, the concept of the company cash flows, and the concept of the Balanced Scorecard (in terms of its financial score). It is depicted that the procedure of the target financial forecasting comprises an appropriate information-accounting support, a target financial forecasting of the company financial position, a target forecasting of the company's cash flows, a development of the specific events (managements' decisions) aimed at overcoming the company's financial difficulties and enhancing its financial position. The author has stated that in the present-day environment the target financial forecasting is an effective instrument of the financial forecasting that enables to set up the base for overcoming the company's financial difficulties and strengthening its financial position. The major fields of the target financial forecasting application are an anticrisis bankrupt company management, a management of the company at the verge of its bankruptcy, as well as a company's investment appeal enhancement (in terms of its financial aspect).
Keywords: 650